Inhibition of Neurogenesis and Induction of Glial Scar Formation by Neuroinflammation Following Ischemic Stroke: Evaluation of BDNF, GFAP, HMGB1 and TNF-α Expressions - Aris Widayati; Fedik Abdul Rantam; Abdulloh Machin; Wibi Riawan (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Ischemic stroke remains as a major health problem and one important process in Ischemic Stroke is neuroinflammation which has a principal role to maintain the balance of neurogenesis and neurodegeneration process in the brain. Neuroinflammation can lead to glial scar and inhibit neurogenesis processes which is needed for recovery neuron function. This study was conducted to observe the role of high mobility group box 1 (HMGB1) and tumor necrosis factor-α (TNF-α) as neuroinflammation markers to glial fibrillary acidic protein (GFAP) as glial scar marker and to brain-derived neurotrophic factor (BDNF) as neurogenesis marker in brain tissue following ischemic stroke.METHODS: Fifteen male Wistar rats were randomized to three groups; sham group, rats receiving occlusion and terminated 180 minutes later (group A), and rats receiving occlusion and terminated after 7 days (group B). Expressions of BDNF and BDNF mRNA were examined using immunohistochemistry (IHC) and Reverse Transcription Polymerase Chain Reaction (RT-PCR), respectively. While GFAP, HMGB1, TNF-α were assessed using IHC.RESULTS: Expression of BDNF was found lower in group A and group B than in sham group (5.20±1.924, 5.00±1.581, and 7.80±1.304, respectively; p=0.032). Expression of BNDF mRNA was found lower in group A and B than in sham group as well. While expression of GFAP was found higher in group A and B than in sham group (9.60±1.517, 11.40±2.074, and 5.20±1.48, respectively; p=0.000). Higher level of HMGB1 and TNF-α expressions were also found to in group A and group B than in sham group (9.3±1.528, 11.67±1.528, and 2.00±1.000, respectively; p=0.000 for HMGB1 and 6.33±1.155, 9.33±1.528, and 3.00±1.000, respectively; p=0.002 for TNF-α).CONCLUSION: The presence of low BDNF levels and high levels of GFAP, HMGB1 and TNF-α markers, possibly reflects inhibition of the neurogenesis process by neuroinflammation, and induced glial scar formation in ischemic stroke conditions after than 180 hours until 7 days. KEYWORDS: ischemic stroke, BDNF, GFAP, TNF-α, HMGB1